Filling in the Gaps: Priming and the Ethics of Pharmaceutical Advertising - Biegler, Paul (Kennedy Institute of Ethics journal, 2015)
, A prime is a cue that makes associated concepts, behaviors, and goals more psychologically accessible to people, influencing their responses in subsequent related environments. I build a case that Direct to Consumer Advertising of Prescription Pharmaceuticals (DTCA) operates as a prime that causes some viewers to prefer and pursue the advertised drug. Drawing on literature from social psychology I show that people subject to priming are mostly unaware of its influence and liable to misattribute the reasons for their primed actions. Misattribution typically includes heightened appraisals of the value of a primed goal. Consistent with this account, I argue that viewers primed by DTCA hold favorable, yet false beliefs about the safety and efficacy of the advertised drug. I further argue that, because those drug properties are material to viewers with the relevant illness, priming in DTCA can undermine the autonomy of their medicine choices. The threat to autonomy posed by priming in DTCA suggests it warrants attention from both regulators and the wider research community. It also adds further reason to be sceptical about the permissibility of this form of advertising.